2016
DOI: 10.1128/mcb.00342-16
|View full text |Cite
|
Sign up to set email alerts
|

Acetylation of Mammalian ADA3 Is Required for Its Functional Roles in Histone Acetylation and Cell Proliferation

Abstract: Alteration/deficiency in activation 3 (ADA3) is an essential component of specific histone acetyltransferase (HAT) complexes. We have previously shown that ADA3 is required for establishing global histone acetylation patterns and for normal cell cycle progression (S. Mohibi et al., J Biol Chem 287:29442-29456, 2012, http://dx.doi.org/10.1074/jbc.M112.378901). Here, we report that these functional roles of ADA3 require its acetylation. We show that ADA3 acetylation, which is dynamically regulated in a cell cycl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 42 publications
1
12
0
Order By: Relevance
“… 6,7 We have also shown that ADA3 itself is acetylated by its interacting KATs. 7 In the present study, we demonstrate that ADA3 acetylation is regulated by growth factor receptor activation through a novel signaling pathway that involves AKT and p300 phosphorylation.…”
Section: Introductionsupporting
confidence: 54%
See 3 more Smart Citations
“… 6,7 We have also shown that ADA3 itself is acetylated by its interacting KATs. 7 In the present study, we demonstrate that ADA3 acetylation is regulated by growth factor receptor activation through a novel signaling pathway that involves AKT and p300 phosphorylation.…”
Section: Introductionsupporting
confidence: 54%
“… 3,27 To begin to explore the mechanistic links between ADA3 and cell proliferation, we recently demonstrated that ADA3 is post-translationally modified by acetylation, and that acetylation is critical for the role of ADA3 to promote cell cycle progression. 7 In this study, we reveal new mechanistic links that control ADA3 acetylation during cell cycle progression downstream of prototype receptor tyrosine kinases of the EGFR family.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Histone post-translational modifications (PTMs) play an important role in diverse processes, such as organismal development, cell differentiation, cell death, and also contribute to cancer development due to epigenetic deregulation ( Berdasco and Esteller, 2010 ; Tan et al, 2011 ). There are many types of histone PTMs including methylation, acetylation, phosphorylation, and histone ubiquitination ( Zhao et al, 2010 ; Tan et al, 2011 ; Zhang et al, 2011 ; Olsen and Mann, 2013 ; Weinert et al, 2013 ; Liu and Gao, 2016 ; Mohibi et al, 2016 ; Nishiyama et al, 2016 ; Penard-Lacronique and Bernard, 2016 ). In recent years, histone lysine crotonylation (Kcr), a new PTM has been discovered.…”
Section: Introductionmentioning
confidence: 99%